2013
DOI: 10.1590/s0101-60832013000400003
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to identify individuals with mild cognitive impairment and Alzheimer's disease using a 30-minute neuropsychological battery?

Abstract: Background: Distinguishing individuals with dementia from those with mild cognitive impairment (MCI) might demand a neuropsychological evaluation. Methods: One hundred and thirty-one consecutive referred elderly patients (37 clinical-controls, 41 with amnestic MCI and 53 with possible/probable AD) were diagnosed with a comprehensive (full) neuropsychological battery, MRI and clinical data. All of the results were blindly coded and evaluated latter with a subset of the tests to reclassify the subjects as MCI, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
2
0
3
Order By: Relevance
“…The neuropsychological battery also addressed other cognitive functions and has been described elsewhere. 8 Our clinical control, MDD, and MCI groups included 25, 16, and 22 individuals respectively. Half of the MCI patients were classified as multiple domain and half were classified as single domain subtype.…”
Section: Sixtymentioning
confidence: 99%
“…The neuropsychological battery also addressed other cognitive functions and has been described elsewhere. 8 Our clinical control, MDD, and MCI groups included 25, 16, and 22 individuals respectively. Half of the MCI patients were classified as multiple domain and half were classified as single domain subtype.…”
Section: Sixtymentioning
confidence: 99%
“…When it comes to identifying MCI, it has been suggested that those subjects may not be discernible from normal aging using basic screening tasks [27]. Hence, assessment of complex cognitive abilities, which rely on processing and integrating data from different cognitive functions, appears to be of greater value for the detection of those cases [28].…”
Section: Introductionmentioning
confidence: 99%
“…Dados epidemiológicos trazem taxas de prevalência de CCL entre 14 e 18% para os indivíduos com idade superior a 70 anos. 6 O CCL representa a transição entre as mudanças cognitivas normais do envelhecimento e as primeiras manifestações clínicas da doença de Alzheimer e pode ser definido como um transtorno em indivíduos que não apresentam demência, mas que relataram deficiências de memória incompatível para a sua idade; contudo, ainda apresentam um desempenho normal em territórios cognitivos e nas atividades de vida diária. 7 É dividido em duas categorias: CCL amnésico e CCL não amnésico, sendo que cada uma destas, apresentam dois subtipos: de domínio simples e de múltiplos domínios.…”
Section: Introductionunclassified